2015
DOI: 10.1016/j.circir.2015.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Factores pronóstico para mortalidad en neonatos con enterocolitis necrosante

Abstract: We must be aware of the factors associated with mortality, as well as those associated with surgical treatment to reduce overall mortality for this condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…Many risk factors, including sepsis, respiratory failure, stage III NEC, intestinal perforation and peritonitis, have previously been reported to be associated with poor outcomes in infants with NEC 10 26 27 28 29 , most of which were also associated with poor prognosis in full-term infants with NEC in the present study. Additionally, patients in the nonsurvivor group more frequently required dopamine support and plasma transfusion relative to survivor group patients.…”
Section: Discussionsupporting
confidence: 58%
“…Many risk factors, including sepsis, respiratory failure, stage III NEC, intestinal perforation and peritonitis, have previously been reported to be associated with poor outcomes in infants with NEC 10 26 27 28 29 , most of which were also associated with poor prognosis in full-term infants with NEC in the present study. Additionally, patients in the nonsurvivor group more frequently required dopamine support and plasma transfusion relative to survivor group patients.…”
Section: Discussionsupporting
confidence: 58%
“…Recent studies confirm the association of deplasmatized red blood cell transfusion for anemia and necrotizing enterocolitis[ 33 - 35 ]. Other studies assessing the effect of administering erythropoietin and iron agents for anemia found a lower incidence of necrotizing enterocolitis[ 33 ].…”
Section: Discussionmentioning
confidence: 87%
“…In more than half of the study subjects (54.5%) that died from GIP, anemia had been diagnosed even before the clinical signs of the diseases that caused GIP. In their recent study, Bracho-Blanchet et al[ 35 ] also identified anemia as a prognostic factor associated with mortality in newborns with necrotizing enterocolitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[47,48] Infection at the surgical site constitutes the primary cause of infection associated with surgical care (40% of postsurgical infections), [19] and is the third leading cause of infection associated with medical treatment in children (14%-16%). [47][48][49][50][51][52] Wound sepsis is preventable but, despite advances in surgical technique, continues to be one of the main challenges in treatment of congenital intestinal malformations. In our study, infectious complications were uncommon, even among patients who did not survive.…”
Section: Original Researchmentioning
confidence: 99%